Translational decadence: versions of Flaubert, Pater, and Lafcadio Hearn - Evangelista, S-M (Cambridge University Press, 2020)
Literary decadence played an active role in promoting the increased circulation and critical scrutiny of literary translations in the second half of the nineteenth century. Building on Walter Benjamin's influential definition of translation as an autonomous literary form, this article examines Walter Pater's “Style” (1888) and Lafcadio Hearn's 1910 translation of Flaubert's Tentation de Saint Antoine (1874) in order to map a theory and practice of decadent translation founded on the aesthetic and ethical respect for the foreignness of the original. Paying closer attention to the aesthetics of decadent translation, as well as its social networks and material history, generates new insights on the cosmopolitan culture of decadence and Victorian literature more broadly.